Histological Pattern of Endometrial Biopsies in Women with Abnormal Uterine Bleeding in a Hospital in North Central Nigeria - Asuzu, Ifeyinwa Mary; Olaofe, Olaejirinde Olaniyi (International Journal of Reproductive Medicine, 2018)
The study is a retrospective cross-sectional study carried out in the Department of Pathology of Premier Hospital, Abuja, on specimens received over a one-year period. Four hundred and eighty-six samples of endometrial biopsies and curettings from women presenting with abnormal uterine bleeding sent to the histopathology laboratory were analyzed. The most common biopsies were those of product of conception which accounted for 304 cases (62.6%). Most of the cases of endometrial hyperplasia were typical. Endometritis and chorioamnionitis were the inflammatory conditions seen. Twenty-three women had molar pregnancies. The most common cause of abnormal uterine bleeding in this population is retained products of conception. There may be need to retrain some of the staff involved in the management of pregnancy related complications. There is need to further evaluate pregnancy related complications to ascertain the causes and circumstances responsible for them so as to appropriately direct interventional protocols.